2022
DOI: 10.1177/1357633x221097469
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of telerehabilitation in patients after total knee replacement: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background Total knee replacement is a commonly adopted surgical intervention to reduce physical limitations and pain in advanced-stage knee osteoarthritis. However, these patients may experience physical dysfunction to limit their access during conventional rehabilitation after total knee replacement. The use of telemedicine may be the promising solution. This study aims to compare the effectiveness of telerehabilitation with conventional in-person rehabilitation in patients who underwent a total knee replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…We observed some differences between the LOS groups (age, sex, RAPT scores), but patients achieved clinically meaningful improvements and positive results for all outcome measures, regardless of hospital LOS. This study supports TelePT as a potential option and aligns with evidence suggesting that TelePT can be comparable to in-person care with lower costs [14,22].…”
Section: Discussionsupporting
confidence: 87%
“…We observed some differences between the LOS groups (age, sex, RAPT scores), but patients achieved clinically meaningful improvements and positive results for all outcome measures, regardless of hospital LOS. This study supports TelePT as a potential option and aligns with evidence suggesting that TelePT can be comparable to in-person care with lower costs [14,22].…”
Section: Discussionsupporting
confidence: 87%
“…In comparison with traditional rehabilitation, only two studies carried out an analysis of efficacy [31,33], both of which position it as equally effective, and even superior in some parameters such as SGRQ [31]; although more studies are needed on this population, telerehabilitation already has a more than proven efficacy in other pathologies [18,43,44] as well as a much lower cost [45,46] and a good reception by patients [24,47]. These aspects make telerehabilitation a new trend in health sciences and, more specifically, boosted by the COVID-19 pandemic [48].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, telerehabilitation can overcome geographical barriers and provide medical care services to people in rural and remote communities and patients with fibromyalgia who cannot attend traditional face-to-face rehabilitation services, which is especially essential during the COVID-19 pandemic [ 39 ]. In addition, although none of the included studies in this meta-analysis reported cost-effectiveness, several previous studies have demonstrated that telerehabilitation can reduce the monetary and time costs of rehabilitation services [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 96%